Does Early versus Delayed Spanning External Fixation Impact Complication Rates for High‐energy Tibial Plateau and Plafond Fractures?. Issue 6 (June 2016) - Haller, Justin M.; Holt, David; Rothberg, David L.; Kubiak, Erik N.; Higgins, Thomas F.
Abstract: Background: High‐energy tibial plateau and tibial plafond fractures have a high complication rate and are frequently treated with a staged approach of spanning external fixation followed by definitive internal fixation after resolution of soft tissue swelling. A theoretical advantage to early spanning external fixation is that earlier fracture stabilization could prevent further soft tissue damage and potentially reduce the occurrence of subsequent infection. However, the relative urgency of applying the external fixator after injury is unknown, and whether delay in this intervention is correlated to subsequent treatment complications has not been examined. Questions/purposes: Is delay of more than 12 hours to spanning external fixation of high‐energy tibial plateau and plafond fractures associated with increased (1) infection risk; (2) compartment syndrome risk; and (3) time to definitive fixation, length of hospitalization, or risk of secondary surgeries? We further stratified our results based on injury site: plateau and plafond. In practical clinical terms, many of these high‐energy C‐type articular fractures will arrive at the regional trauma center in the evening and this investigation attempted to explore if these injuries need to be placed in temporizing fixators that evening or if they may be safely addressed in a dedicated trauma room the next morning. Methods: We performed a retrospective review of all patients at a Level I university trauma center with high‐energy tibial plateau and plafond fractures who underwent staged treatment with a spanning external fixation followed by subsequent definitive internal fixation between 2006 and 2012. Patients who received a fixator within 12 hours of recorded injury time were classified as early external fixation; those who received a fixator greater than 12 hours from injury were classified as delayed external fixation. There were 80 patients (42 plateaus and 38 plafonds) in the early external fixation cohort and 79 patients (45 plateaus and 34 plafonds) in the delayed external fixation cohort. Deep infection rate was 13% in plateau fractures and 18% in plafond fractures. Rates of infection, compartment syndrome, secondary surgeries, time to definitive fixation, and length of hospitalization were recorded. Results: Controlling for differences in open fracture severity between groups, there was no difference in infection for plafond (early fixation: 12 of 38 [32%]; delayed fixation: seven of 34 [21%]; adjusted relative risk = 1.39 [95% confidence interval CI, 0.45‐4.31], p = 0.573) and plateau (early fixation: eight of 42 [19%]; delayed fixation: nine of 45 [20%]; adjusted relative risk: 0.93 [95% CI, 0.31‐2.78], p = 0.861) groups. For compartment syndrome risk, there was no difference between early and delayed groups for plateau fractures (early fixation: six of 42 [14%]; delayed fixation: three of 45 [7%]; relative risk = 0.47 [0.12‐1.75], p = 0.304) and plafond fractures (early fixation: two of 38 [5%]; delayed fixation: three of 34 [9%]; relative risk = 1.67 [0.30‐9.44], p = 0.662). There was no difference for length of hospitalization for early (9 ± 7 days) versus delayed fixation (9 ± 6 days) (mean difference = 0.24 [95% CI, −2.9 to 3.4], p = 0.878) for patients with plafond fracture. Similarly, there was no difference in length of hospitalization for early (10 ± 6 days) versus delayed fixation (8 ± 4 days) (mean difference = 1.6 [95% CI, −3.9 to 0.7], p = 0.170) for patients with plateau fracture. Time to definitive fixation for plateau fractures in the early external fixation group was 8 ± 6 days compared with 11 ± 7 days for the delayed external fixation group (mean difference = 2.9 [95% CI, 0.13‐5.7], p = 0.040); there was no difference in time to definitive fixation for early (12 ± 7 days) versus delayed (12 ± 6 days) for patients with plafond fractures (mean difference = 0.39 [95% CI, −2.7 to 3.4], p = 0.801). There was no difference in risk of secondary surgeries between early external fixation (21 of 38 [55%]) and delayed external fixation (13 if 34 [38%]) for plafond fractures (adjusted relative risk = 0.69 [95% CI, 0.41‐1.16], p = 0.165) and no difference between early fixation (24 of 42 [57%]) and delayed fixation (26 of 45 [58%]) for plateau fractures (adjusted relative risk = 1.0 [95% CI, 0.70‐1.45], p = 1.00). Conclusions: We were unable to detect a difference in infection, compartment syndrome, secondary procedures, or length of hospitalization for patients who undergo early versus delayed external fixation for high‐energy tibial plateau or plafond fractures. This may affect decisions for resource use at trauma centers such as whether high‐energy periarticular lower extremity fractures need to be spanned on the evening of presentation or whether this procedure may wait until the morning trauma room. Given the high complication rate of these injuries and clinical relevance of this question, this may also need to be examined in a prospective manner. Level of Evidence: Level IV, therapeutic study.